Analisis Keterjangkauan Properti Residensial Pada Wilayah Jawa-Bali - Restiana Dewi (Fakultas Ekonomika dan Bisnis, Universitas Diponegoro, 2022)
In addition to the problem of the availability of residential stock from the supply side, there are problems from the demand side regarding people's purchasing power in reaching housing prices, or often referred to as afordability problems. This study investigates the affordability of the median income group and the lowest 40% income group from the expenditure approach of the national economic survey (susenas, 2020). The calculation of affordability using the installment affordability index approach, with the object of research in the Java-Bali region consisting of DKI Jakarta, West Java, Central Java, East Java, DI Yogyakarta, Banten and Bali. The results showed that the installment affordability index (IKC) in the DKI Jakarta and Banten areas showed a value above 1, this means that the community is still able to reach small-type residential property loan installments according to the price limit for treaded welfare homes set by the Ministry of Public Works and Public Housing. (PUPR). However, for people in West Java, Central Java, East Java, Yogyakarta and Bali, the IKC value is below 1, meaning that with a median income and an upper limit of 40% of the lowest income in these areas cannot reach small-type housing installments. The problem of affordability will become a development problem, especially in achieving the SDG's goals which have a target in 2030, the community has access to adequate, safe, and affordable housing.